2015
DOI: 10.1007/s10815-015-0575-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ovarian stimulation after treatment with chemotherapy

Abstract: Purpose Chemotherapeutic agents have a known gonadotoxic effect; however, it is difficult to predict the impact they may have on ovarian stimulation. The objective of this study was to evaluate response to ovarian stimulation in patients exposed to chemotherapy compared with patients who were chemotherapy-naïve. Methods A retrospective cohort study of 130 patients with cancer or autoimmune disease was performed. Demographics, ovarian reserve, ovarian response and stimulation parameters, and oocyte data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Young women with malignancies are generally counseled on the potential detrimental effects of cancer treatments on future fertility and on the possible benefits of fertility preservation techniques [1][2][3][4][5]. In most cases, this counseling occurs in an urgent setting because delay in the initiation of treatments is generally perceived as potentially detrimental for survival [2] and the techniques for fertility preservation need some time to be done (from days to weeks).…”
Section: Introductionmentioning
confidence: 99%
“…Young women with malignancies are generally counseled on the potential detrimental effects of cancer treatments on future fertility and on the possible benefits of fertility preservation techniques [1][2][3][4][5]. In most cases, this counseling occurs in an urgent setting because delay in the initiation of treatments is generally perceived as potentially detrimental for survival [2] and the techniques for fertility preservation need some time to be done (from days to weeks).…”
Section: Introductionmentioning
confidence: 99%
“…AMH is exclusively synthesized by granulosa cells during the early stages of follicular development 38 , and AMH serum concentration is an important measure of ovarian reserve 39 . Additionally, the effect of gonadotoxic agents on ovarian follicular development is reflected by lower serum concentrations of AMH 40,41 . Moreover, low AMH levels are prognostic for poor probability of spontaneous conception as well as poor response to ART 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a significant decrease in ovarian response to IVF in cancer patients who had undergone chemotherapy [ 9 10 ]. In a cohort study, regardless of the type of cancer, response to gonadotropins and the number of oocytes retrieved were significantly decreased in the post-chemotherapy group [ 10 ]. Our study shows similar results as the previous study of Chan et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study, regardless of the type of cancer, response to gonadotropins and the number of oocytes retrieved were significantly decreased in the post-chemotherapy group [ 10 ]. Our study shows similar results as the previous study of Chan et al [ 10 ]. which showed higher cancellation rates in post-chemotherapy patients than in chemotherapy-naïve patients.…”
Section: Discussionmentioning
confidence: 99%